ChemInform Abstract: Platinum‐Catalyzed Tandem Indole Annulation/Arylation for the Synthesis of Diindolylmethanes and Indolo[3, 2‐b]carbazoles. Issue 2 (14th January 2014) - Shu, Dongxu; Winston‐McPherson, Gabrielle N.; Song, Wangze; Tang, Weiping
Abstract The scope of different indoles and propargylic ethers is examined for the tandem annulation/arylation cascade reaction.